2014
DOI: 10.5194/se-5-713-2014
|View full text |Cite
|
Sign up to set email alerts
|

Methodological interference of biochar in the determination of extracellular enzyme activities in composting samples

Abstract: Abstract. Biochar application has received increasing attention as a means to trap recalcitrant carbon and enhance soil fertility. Hydrolytic enzymatic assays, such as β-glucosidase and phosphatase activities, are used for the assessment of soil quality and composting process, which are based on use of p-nitrophenol (PNP) derivatives as substrate. However, sorption capacity of biochar can interfere with colorimetric determination of the hydrolysed PNP, either by the sorption of the substrate or the reaction pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…Similarly, several other studies showed shifts in enzyme activities induced by biochar addition [65,85]; for instance, alkaline phosphomonoesterase activities were increased, whilst acidic phosphomonoesterase activities were inhibited by addition of biochar regardless of soil types [86,87]. However, this effect could have been partly due to the absorption of the substrate or enzymes, which occurs more strongly at lower pH rather than at a higher one [88,89]. In fact, the study performed by Masto et al [90] showed that both alkaline and acid phosphomonoesterase activities increased in red soils with addition of the biochar produced from Eichornia.…”
Section: Enhancement Of P Solubilisation and Mineralisation By Alterimentioning
confidence: 67%
“…Similarly, several other studies showed shifts in enzyme activities induced by biochar addition [65,85]; for instance, alkaline phosphomonoesterase activities were increased, whilst acidic phosphomonoesterase activities were inhibited by addition of biochar regardless of soil types [86,87]. However, this effect could have been partly due to the absorption of the substrate or enzymes, which occurs more strongly at lower pH rather than at a higher one [88,89]. In fact, the study performed by Masto et al [90] showed that both alkaline and acid phosphomonoesterase activities increased in red soils with addition of the biochar produced from Eichornia.…”
Section: Enhancement Of P Solubilisation and Mineralisation By Alterimentioning
confidence: 67%
“…Biochar is composed of recalcitrant carbon from microbial degradation and of a charged surface with organic functional groups; therefore, it can increase soil organic carbon (SOC) levels and C stocks [ 20 23 ]. Biochar application could produce agronomic benefits, particularly fertility maintenance, SOC sequestration, and crop production [ 5 , 8 , 24 26 ]. However, few studies have examined the benefits of biochar application on the hydraulic properties and erosion recalcitrant of soil.…”
Section: Introductionmentioning
confidence: 99%
“…β-glucosidase activity was determined based on p-nitrophenol (PNP) quantification at 415 nm (Eivazi & Tabatabai 1988). To correct for biochar interference (Jindo, Matsumoto, Izquierdo, Sonoki, & Sanchez-Monedero, 2014a) on the release of PNP, an additional set of samples was analyzed. Instead of the substrate (p-Nitrophenyl-β-D-glucopyranoside [PNG]), the reaction product (PNP) was added at the beginning of the incubation at concentrations of 100, 200, 300, and 500 nmol ml −1 (equivalent to 5 × 10 5 nmol PNP kg soil −1 ).…”
Section: Enzyme Activity and P-nitrophenol Retentionmentioning
confidence: 99%